(untitled) (Scientific journal of the Fergana State University, 2025)
This article aims to achieve a high-quality grain yield by improving winter wheat cultivation agrotechnologies of foliar feeding of liquid nitrogen fertilizers to increase winter wheat productivity and grain quality.